Spin Wave Analysis of Quasi Two-Dimensional Quantum Magnet Cs2CuCl4 - Zhang, Junhua (My University, 2005)
The inelastic neutron scattering measurements by Coldea and co-workers on Cs2CuCl4 have attracted intense attention due to the anomalous spin correlation properties revealed. The debate on the low-temperature magnetic phase, spiral ordered phase or spin liquid phase, of this material has triggered mainly two theoretical scenarios, a spin wave scenario and a spinon scenario, for the origin of the unusual scattering continua and large quantum effects. Since there is evidence of low-energy spin wave modes in the experimental data, a study of the spiral ordered phase using perturbation theory, taking into account spin wave interactions, becomes important to determine the nature of the magnetic excitations in this spin system.
Motivated by this situation, we have carried out a perturbation calculation within the nonlinear spin wave theory framework by means of the 1/S expansion scheme. In this work, we first develop the general formalism for a class of spiral ordered spin systems. Then we explain how to make contact between our theoretical calculation and experiment. After establishing the necessary formulae, we perform numerical evaluations for Cs2CuC14 to compare with experimental data. We find that a nonlinear spin wave analysis of this material results in significant continua in the scattering spectra as well as large quantum renormalization of the excitation energy. However, our results are quantitatively different from the experimental data. Further numerical work needs to be done to better understand the remaining discrepancies between theory and experiment.
Title: Spin Wave Analysis of Quasi Two-Dimensional Quantum Magnet Cs2CuCl4, Author: Junhua Zhang, Location: Thode